The use of Twitter as a strategic dialogue platform for IBEX35 companies during the pandemic - Miquel-Segarra, Susana (2023)
This paper analyses the communication carried out by IBEX35 companies in crisis situations in order to determine the mechanisms that try to favour dialogue between organisations and their stakeholders. The sample is made up of the tweets that include the word covid and that have been issued by the 27 IBEX 35 companies that had verified corporate profiles on the Twitter social platform during the first 6 months of the COVID-19 pandemic in Spain. Taking into consideration the dialogic principles established by Kent and Taylor (1998), which were adapted by Rybalko and Seltzer (2010) for Twitter, an adaptation was made to establish indicators to apply to the conversation established on the platform. To analyse the differences in interaction, the t-test for independent samples and the one-factor ANOVA were used. The results show that companies maintain an interest in engaging with their audiences but continue to deal with topics that are not of interest to users, which makes it difficult for a dialogue or conversation to take place between companies and stakeholders. The article shows that the resources most used by companies in crisis situations are the call to action and dialogue, either by asking their users questions or suggesting the desired interaction. While directly asking users for their opinions does not generate more dialogue, the results show that soliciting attitudes, such as commenting, sharing an image or liking an image, does increase interaction. This implies that there is low interest on the part of audiences to join a real conversation.